The Persuasion Knowledge Model: How People Cope with Persuasion Attempts - Friestad, Marian; Wright, Peter (Journal of Consumer Research, 1994)
Abstract In theories and studies of persuasion, people's personal knowledge about persuasion agents' goals and tactics, and about how to skillfully cope with these, has been ignored. We present a model of how people develop and use persuasion knowledge to cope with persuasion attempts. We discuss what the model implies about how consumers use marketers' advertising and selling attempts to refine their product attitudes and attitudes toward the marketers themselves. We also explain how this model relates to prior research on consumer behavior and persuasion and what it suggests about the future conduct of consumer research.